2017
DOI: 10.1364/boe.8.002458
|View full text |Cite
|
Sign up to set email alerts
|

In vivo volumetric quantitative micro-elastography of human skin

Abstract: Abstract:In this paper, we demonstrate in vivo volumetric quantitative micro-elastography of human skin. Elasticity is estimated at each point in the captured volume by combining local axial strain measured in the skin with local axial stress estimated at the skin surface. This is achieved by utilizing phase-sensitive detection to measure axial displacements resulting from compressive loading of the skin and an overlying, compliant, transparent layer with known stress/strain behavior. We use an imaging probe h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 45 publications
0
18
0
Order By: Relevance
“…Further, it may find application in the cosmetics industry, where the mechanical properties of skin are important in aging, treatment and regeneration [33]. The first steps toward this with OCE have been recently demonstrated, showing the capacity to distinguish burn scars, moles and image other locations of the skin, however, all based on the algebraic method [34]. The iterative reconstruction method presented here will likely further improve the clinical diagnostic capacity of OCE.…”
Section: Ex Vivo Malignant Breast Tumormentioning
confidence: 92%
“…Further, it may find application in the cosmetics industry, where the mechanical properties of skin are important in aging, treatment and regeneration [33]. The first steps toward this with OCE have been recently demonstrated, showing the capacity to distinguish burn scars, moles and image other locations of the skin, however, all based on the algebraic method [34]. The iterative reconstruction method presented here will likely further improve the clinical diagnostic capacity of OCE.…”
Section: Ex Vivo Malignant Breast Tumormentioning
confidence: 92%
“…To date, clinical feasibility studies in OCE have largely been performed using bulky, labbased, bench-top setups [11,12], unsuitable for use in many clinical settings. In one preliminary study, OCE on skin was demonstrated in a quasi-handheld format where supporting apparatus was required to stabilize the probe [13]. However, a fully handheld probe would greatly facilitate the continued clinical development of OCE.…”
Section: Introductionmentioning
confidence: 99%
“…The probe utilizes a microelectromechanical system (MEMS) mirror to scan the beam across the sample surface. The small footprint of the MEMS module (8 × 8 × 3 mm), incorporated with a small scanning mirror (3 mm in diameter), facilitates a far more compact handheld probe than is achievable using the galvanometer-based scanners used previously in QME [12,13,23]. In addition, our QME probe incorporates a custom annular lead zirconate titanate (PZT) actuator, providing uniform, periodic mechanical loading to the tissue, combined with a two-section compliant silicone layer, to estimate the stress at the tissue surface.…”
Section: Introductionmentioning
confidence: 99%
“…However, the mechanical behavior of the skin is of importance in its barrier function against mechanical external aggressions and so on . Although several clinical examinations pointed out the relationships between mechanical properties and skin disease or signs of aging, only a few studies have analyzed the mechanical properties and behavior of SEs . Tupin et al demonstrated that the elastic modulus and viscosity increased with the addition of epidermis to dermis in an SE by an indentation and relaxation test .…”
Section: Introductionmentioning
confidence: 99%